REGARDING THE WORK DONE IN THE AREA OF OVERSEEING THE ENFORCEMENT OF LEGISLATION RELATED TO THE PROTECTION OF ATMOSPHERIC AIR - K.T. Almatov (Journals Park Publishing, 2024)
The article describes the problem of air pollution in cities, including the types of atmospheric pollution and methods to minimize their negative impacts.
Keywords: atmospheric air, tmospheric pollution, harmful emissions